An analysis of price disparity: Peninsular Malaysia and Sabah - Siti Marsila Mhd Ruslan,; Kasypi Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the price differences between Peninsular Malaysia and Sabah from 2004 using quantitative and qualitative methods. For quantitative research, we employ disaggregate monthly consumer price indices for nine types of goods and services. Based on the Johansen co-integration test, the results reveal that the long-run relationship only exists for transport group. The findings using Granger pair-wise causality test indicated that the prices in Peninsular Malaysia do not determined the price in Sabah. Qualitative research was further conducted via interviews with stakeholders of shipping providers, port authority, government and special interest group show that the price disparity between Peninsular Malaysia and Sabah occurred due to trade imbalance, sluggish economic activities, poor accessibility between port and retailers, insufficient infrastructure and technical facilities and political sentiment.